A Study of Appadurai’s idea of Cultural Homogenization in Arvind Adiga’s The White Tiger - Mahnoor Sardar; Kashifa Khalid; Usama Javed Iqbal (Journal of Research in Humanities, 2022)
This study examines the concept of Cultural Homogenization as one of the root causes of globalization in the Indian society. The study narrows down by applying a major global scape, Ethnoscape proposed by Arjun Appadurai to explore contemporary globalized Indian culture in The White Tiger by Arvind Adiga. The novel portrays that the globalization in the Indian society propagates the idea of Americanization. Therefore, globalization here is taken in a negative connotation as the research also sheds lights that the arrival of the global culture in postcolonial Indian society is basically propagation of American Imperialism. This imposition of American imperialist culture and selective globalization intensifies the class stratification that eventually catalyzes the internal migrations. The study claims that this huge influx of people and information through technological resources causes loss of individualism and native identity when cultural globalization encourages a ‘western ideal’. Therefore, with a foremost exploration to analyze the influence globalization has upon culture, this study aims to back up the uniqueness of national cultures amid homogenized world culture.